KONSTRUKSI PEMIKIRAN TASAWUF WUJUDIYAH DALAM NASKAH AMBULUNG DI KALIMANTAN SELATAN - Nur Kolis (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2020)
This article aims to refute the opinion that states, Sufism as a static construction of orthodox thought. It is done by looking deeply into the dynamic dimensions of Sufism and capturing the side of transformation that occurs, as seen in the Ambulungmanuscript in South Kalimantan. Starting from three main issues, related to; mapping the contextual (transformative) dimensions of Sufism in the Ambulung manuscript; various factors influencing the transition of Sufism understanding construction in the Ambulung manuscript; and the construction process of Sufism’s teaching concept in the Ambulungmanuscript, the results of the study show that the Sufism’s teaching in the Ambulung manuscript is a wujudiyyah concept which is full of controversy in the Islamic history. This manuscript is only studied by the sir (special or limited) community, whose participants are limited for Sufism teachers. Not for the public audience, because of its teachings are considered potentially being misunderstood. The teachings contained in this manuscript, indirectly persuade people to dynamically think moderately,through understanding tauhid wujudiyyah which are tolerant and openness to the diversity.